Clinical and genetic characteristics of children with COX20-associated mitochondrial disorder: case report and literature review - Liqing Chen; Yan Liu (BMC, 2023)
Abstract Background The deficiency of cytochrome c oxidase 20 is a rare autosomal recessive mitochondrial disorder characterized by ataxia, dysarthria, dystonia and sensory neuropathy. Case presentation In this study, we describe a patient from a non-consanguineous family exhibiting developmental delay, ataxia, hypotonia, dysarthria, strabismus, visual impairment and areflexia. An examination of nerve conduction showed a normal result at first but revealed axonal sensory neuropathy later. This situation has not been reported in any literatures. The whole-exome sequencing analysis revealed that the patient harbored compound heterozygous mutations (c.41 A > G and c.259G > T) of the COX20 gene. By literature review, 5 patients carried the same compound heterozygous mutations. Conclusion COX20 might be considered as a potential gene for the early-onset ataxia and the axonal sensory neuropathy. Our patient exhibited strabismus and visual impairment, which expands the clinical presentation of COX20 related mitochondrial disorders caused by the compound heterozygous variants (c.41 A > G and c.259G > T). However, a clear genotype/phenotype correlation has not yet been established. Additional researches and cases are needed to further confirm the correlation.